Critical Framing Analysis: Violence Against Women on Online Media - Sunarto Sunarto; Amida Yusriana; Mutia Rahmi Pratiwi; Citra Safira (Ikatan Sarjana Komunikasi Indonesia, 2023)
The journalistic problem that arises when covering women issues at national and global levels showed that the dominant issues in the mass media were masculine. Women issues were dominant in alternative media. It was assumed that the alternative media use feminist journalism framing in its content. This research used media framing theory as the second level of agenda-setting theory that is supported by standpoint theory in critical paradigm to understand the phenomena. It used descriptive-qualitative approach with critical framing analysis design. The object of study covered 39 articles in February 2022 edition of Konde.Co and Magdalene.Co. The alternative media were chosen because they had feminist vision. The data was analyzed using Robert T. Entmant’s procedure, namely: define problem; diagnosis of causes; make moral judgments; and treatment recommendations. The results showed that almost all the existing articles applied the principles of feminist journalism. The framing of women-related news was more dominant particularly the issue of violence against women. This issue was dominant since until right now it is still happening actually in society. Violence is used by men to subjugate women. Patriarchal power relations are assumed to be behind this phenomenon. This research concluded that the framing of feminist journalism focused on violence against women in public domain committed by men abusers in the position as husbands, lovers, teachers, friends, medical workers, co-workers or public figures. Patriarchism gave men the privilege of using violence as a natural thing to do. Being a feminist man and empowered woman, as well as firm law enforcement were recommendations emphasized in this framing.